ANALISIS FRAMING PEMBERITAAN PROGRAM VAKSINASI COVID-19 - Habib Muhsin; Fadjarini Sulistyowati; Irsasri Irsasri (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
The pandemic has been going on for a year, Indonesia, like other countries, has been constructing some policies in dealing with it. One of the policies is vaccination program, which is a step to create herd immunity. The role of mass media in informing government’s program is extremely significant. However, mass media does not work in a vacuum, there is a frame by which they construct some phenomenon into a news. This research is done to understand the media construction made by detik.com and Kompas.com in their vaccination news. Robert N. Entman’s framing analysis is being used. Using framing technique, the role of media in constructing certain phenomenon can be found. Vaccination news can be categorized into three: 1) Framing towards news regarding President; 2) Framing towards news regarding people’s disbelief in vaccination and 3) Framing towards vaccine management and data. This research shows that detik.com and Kompas.com has biases towards government’s policies in vaccination program. Aside from supporting the policies, both medias have some control for those policies. This control can be shown by their introducing the vaccine program to society. The people’s disbelief in the vaccines indicates the lack of the government’s participation in the vaccine’s introduction and exposure. This is also true in regards to vaccine management and data. In conveying information, Kompas.com is more informative and comprehensive.